1999
DOI: 10.1021/jo990618v
|View full text |Cite
|
Sign up to set email alerts
|

Stereospecific (Conrotatory) Photochemical Ring Opening of Alkylcyclobutenes in the Gas Phase and in Solution. Ring Opening from the Rydberg Excited State or by Hot Ground State Reaction?

Abstract: The photochemistry of 1,2-dimethylcyclobutene and cis- and trans-1,2,3,4-tetramethylcyclobutene has been studied in the gas phase (1 atm; SF6 buffer) and in hydrocarbon solvents with 193-, 214-, and 228-nm light sources. The major products are the isomeric dienes from electrocyclic ring opening and 2-butyne + alkene (ethylene or E-/Z- 2-butene) due to formal [2+2]-cycloreversion. The total yields of dienes relative to 2-butyne are generally higher in the gas phase than in solution but decrease with increasing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 46 publications
(103 reference statements)
2
16
0
Order By: Relevance
“…In this case, ring opening occurs with perfect conrotatory selectivity, i.e., in anti-WH direction, as found by Leigh and Cook [115]. It was therefore first supposed that the reaction actually takes place in the hot ground state; but this was soon disproved by the same authors [116].…”
Section: Predistortion By Momenta Generated In Preceding Statesmentioning
confidence: 67%
See 1 more Smart Citation
“…In this case, ring opening occurs with perfect conrotatory selectivity, i.e., in anti-WH direction, as found by Leigh and Cook [115]. It was therefore first supposed that the reaction actually takes place in the hot ground state; but this was soon disproved by the same authors [116].…”
Section: Predistortion By Momenta Generated In Preceding Statesmentioning
confidence: 67%
“…The Leigh group observed that cycloreversion is generally increased, if the Rydberg instead of the pp* state is excited [115,117]. They also found that at least part of the ring cleavage takes place via intermediate formation of cyclopropyl carbenes (that also deliver methylene cyclopropanes as end products) by ring contraction (alkyl 1,2-migration, Scheme 13) [118] (it is also conceivable that carbene formation and ring splitting result from the same conical intersection).…”
Section: Predistortion By Momenta Generated In Preceding Statesmentioning
confidence: 99%
“…The direct irradiation of simple alkylcyclobutenes in the gas phase or solution results in electrocyclic ring opening and stereospecific [2 + 2]-cycloreversion to yield the corre-sponding alkyne and alkene (1)(2)(3)(4). It has been known for several years that contrary to early indications (5), the ring opening reaction proceeds nonstereospecifically (6,7), in apparent violation of simple orbital symmetry selection rules for photoelectrocyclic reactions (8) as well as the results of high level ab initio calculations (9,10), all of which predict that the process should proceed with preferred disrotatory stereochemistry when initiated by population of the lowest π,π* excited singlet state of the molecule.…”
Section: Introductionmentioning
confidence: 99%
“…It has been known for several years that contrary to early indications (5), the ring opening reaction proceeds nonstereospecifically (6,7), in apparent violation of simple orbital symmetry selection rules for photoelectrocyclic reactions (8) as well as the results of high level ab initio calculations (9,10), all of which predict that the process should proceed with preferred disrotatory stereochemistry when initiated by population of the lowest π,π* excited singlet state of the molecule. Assuming that orbital symmetry selection rules are, in fact, obeyed in the π,π* reaction, there are at least three possible explanations for this behaviour (6): (i) ring opening proceeds adiabatically, yielding the photochemically allowed (disrotatory) diene isomer(s) in the lowest π,π* excited singlet state, from which the forbidden (thermally allowed, conrotatory) isomer(s) are formed via E,Z-isomerization; (ii) the conrotatory isomers are formed via reaction from upper vibrational levels of the ground state of the cyclobutene, populated by internal conversion in competition with disrotatory π,π* state ring opening; and (iii) the conrotatory isomers are formed via competing reaction of the radical-cation-like π,R(3s) Rydberg excited singlet state, which is known to be of similar energy to the π,π* (valence) singlet state in alkylcyclobutenes (4,11,12), just as it is in other aliphatic alkenes (13)(14)(15). 2 Much of our work in this area over the past 15 years has been directed at attempting to distinguish between these possibilities, through studies of the effects of substituents, excitation wavelength, and various structural constraints on the stereochemistry of the reaction (4,6,12,(16)(17)(18)(19)(20)(21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation